The Impact of Mobile-Based Calendar Applications for Digitalizing Scheduling Management on Community Participation and Awareness in Traditional Villages - Oktarini, Luh Nik; Asmarajaya, I Kadek Andy (Jurnal Ilmiah Manajemen & Bisnis, 2024)
This study aims to investigate the impact of implementing a mobile-based scheduling information system in the Desa Adat Tuban. The research focuses on enhancing information services provided by village officials, as well as increasing community participation and awareness. The methodology involves data collection through surveys and structured interviews, which are subsequently analyzed to assess the system’s usability and effectiveness within the traditional village context. The system’s usability score reached 64.2 percent, classified as “Good,” though there is potential for further system refinement. The correlation between system implementation and service effectiveness reached 0.348, indicating that although a relationship exists, its influence remains limited. The system explains 12.11 percent of the variance in service effectiveness, highlighting the influence of external factors beyond the system itself. These findings emphasize the practical contribution of this system to traditional village management, underscoring areas where technological integration can support community engagement. From a managerial perspective, this study recommends mobile-based system implementation as an initial step, to be followed by feature adjustments based on user feedback and enhanced training to improve long-term effectiveness. The study further recommends prioritizing user feedback in future design iterations, regular usability testing, and training for village officials and community members to maximize system effectiveness. Additionally, collaboration with technology experts may assist in aligning system features with the unique cultural and operational context of the traditional village. In alignment with a focus on community-centered innovations, this study highlights the potential of mobile-based scheduling systems to transform information management in traditional village environments, dependent upon ongoing usability improvements and active community engagement.